HA-1H T-Cell Receptor Gene Transfer to Redirect Virus-Specific T Cells for Treatment of Hematological Malignancies After Allogeneic Stem Cell Transplantation: A Phase 1 Clinical Study - van Balen, Peter; Jedema, Inge; van Loenen, Marleen M.; de Boer, Renate; van Egmond, H. M.; Hagedoorn, Renate S.; Hoogstaten, Conny; Veld, Sabrina A. J.; Hageman, Lois; van Liempt, P. A. G.; Zwaginga, Jaap-Jan; Meij, Pauline; et al. (Frontiers in Immunology, 2020)
Graft-versus-leukemia (GVL) reactivity after HLA-matched allogeneic stem cell transplantation (alloSCT) is mainly mediated by donor T cells recognizing minor histocompatibility antigens (MiHA). If MiHA are targeted that are exclusively expressed on hematopoietic cells of recipient origin, selective GVL reactivity without severe graft-versus-host-disease (GVHD) may occur. In this phase I study we explored HA-1H-TCR gene transfer into T cells harvested from the HA-1H negative stem-cell donor to treat HA-1H positive HLA-A*02:01 positive patients with high-risk leukemia after alloSCT. HA-1H is an hematopoiesis-restricted MiHA presented in HLA-A*02:01. Since we previously demonstrated that donor-derived virus-specific T-cell infusions did not result in GVHD, we used donor-derived EBV and/or CMV-specific T-cells to be redirected by HA-1H-TCR. EBV and/or CMV-specific T-cells were purified, retrovirally transduced with HA-1H-TCR, and expanded. Validation experiments illustrated dual recognition of viral antigens and HA-1H by HA-1H-TCR-engineered virus-specific T-cells. Release criteria included products containing more than 60% antigen-specific T-cells. Patients with high risk leukemia following T-cell depleted alloSCT in complete or partial remission were eligible. HA-1H-TCR T-cells were infused 8 and 14 weeks after alloSCT without additional pre-conditioning chemotherapy. For 4/9 included patients no appropriate products could be made. Their donors were all CMV-negative, thereby restricting the production process to EBV-specific T-cells. For 5 patients a total of 10 products could be made meeting the release criteria containing 3-280x10^6 virus and/or HA-1H-TCR T-cells. No transfusion related toxicity occurred. One patient with relapsed AML at time of infusions died due to rapidly progressing disease. Four patients were in remission at time of infusion. Two patients died of infections during follow-up, not likely related to the infusion. Two patients are alive and well without GVHD. In 2 patients persistence of HA-1H-TCR T-cells could be illustrated correlating with viral reactivation, but no overt in-vivo expansion of infused T-cells was observed. In conclusion, HA-1H-TCR-redirected virus-specific T-cells could be made and safely infused in 5 patients with high-risk AML, but overall feasibility and efficacy was too low to warrant further clinical development using this strategy. New strategies will be explored using patient-derived donor T-cells isolated after transplantation transduced with HA-1H-specific TCR to be infused following immune conditioning.